Factors predicting proper handwashing practice amidst the COVID-19 pandemic in India: a field-based cross-sectional study. (29th September 2022) - Gupta, Shibaji; Das, Debasis; Chakraborty, Arup; Banerjee, Rudradeep
Abstract: Proper handwashing is one of the effective ways to prevent many communicable diseases, including COVID-19. We explored the handwashing practices in a rural Indian population before the probable third wave of the COVID-19 pandemic. A data collection schedule was administered to eligible adult members of a rural community, selected by multi-stage sampling, to assess their pattern and practice of handwashing. All 176 respondents washed their hands after defecation, 82.4 and 80.7% washed hands after urination and before taking food, respectively, while 68.2% of respondents washed hands after coming back from outdoors. Among those who handwashed, 82.9% used soap water after defecation; 46.2, 45.8 and 50.8% washed hands with soap water after urination, before taking food and after visiting outdoors, respectively. Only a quarter (24.4%) of all the participants used soap water for handwashing consistently after defecation, after urination, before taking food and after coming home. The more educated, those coming from higher socioeconomic stratum and working from home, were more likely to report proper handwashing practice. Handwashing, as recommended by health agencies, for restraining COVID-19 infection, was not noticed in the majority of the participants. Better awareness of handwashing is recommended to help restrain COVID-19 in the Indian population. HIGHLIGHTS: Global health bodies stress upon proper handwashing as one of the effective ways to curb the COVID-19 pandemic, but this study reveals an unsatisfactory state of handwashing practice in rural India. Handwashing was not universal among the participants for all the indicators; the use of soap water during handwashing was not a commonly noted practice. None were found to follow all the recommended steps of handwashing. Graphical Abstract